PENGARUH KOMITMEN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. WAHANA SEMESTER LINGGAU (HARIAN PAGI LINGGAU POS) - Suyadi, Suyadi; Putri, Inne Destina (Jurnal Media Ekonomi (JURMEK), 2020)
The purpose of this study was to determine the effect of commitment and job satisfaction on employee performance at PT. Wahana Semester Linggau (Daily Morning Linggau Pos) Lubuklinggau City. The method used is quantitative. The sample consisted of 32 people. The results of the study are the results of data analysis and discussion that has been described in the previous chapter, it can be concluded that 1) The results of the t test above can explain that the variable Commitment to Employee Performance at PT. Wahana Semester Linggau shows that tcount = 4.336 is greater than ttable = 2.042 with dk = 32 and a significant level of sig = 0.004, this means that partially the commitment variable has a significant effect on employee performance at PT. Linggau Semester rides. This proves the hypothesis in the research is proven and the hypothesis is accepted. 2) The results of the t test explain that the variable job satisfaction on employee performance at PT. Wahana Semester Linggau shows that tcount = 5.388 is greater than ttable = 2.042 with dk = 32 and a significant level of sig = 0.001, this means that partially the Job Satisfaction variable has a significant effect on Employee Performance at PT. Linggau Semester rides. This proves the hypothesis in the research is proven and the hypothesis is accepted. 3) The value of Fcount> Ftable means that Ho is rejected and Ha is accepted, meaning that the Commitment variable (X1) and the Job Satisfaction variable (X2) have a significant effect on Employee Performance (Y) at PT. Linggau Semester rides.